Breast Cancer and Nutrition: A Paradigm for Prevention in 3D Across the Life Course - Forman, Michele R. (Frontiers in Oncology, 2020)
Breast cancer, the most common cancer in women worldwide, has recognized reproductive and anthropometric risk factors including age at menarche and adult height. Yet the age when a woman attains her adult height or experiences menarche for example is simply the timing of the major life event at the end of a long trail of exposures that began in utero. The objective of this article is to investigate through a review of the literature the role of nutrition in breast cancer prevention through three dimensions (D). Each D offers a different lens. The First D identifies windows/ages of exposures or conditions that convey vulnerability or protection from breast cancer. The Second D addresses the intensity and duration of the exposure; and the (Third D) examines the pace i.e. how rapid or slow the young woman experiences her growth and development. Birthweight illustrative of the First D reveals a strong signal across the life course on BC risk, but the risk group varies from low to high birthweight. Stressful life events like being a pubertal aged girl living in a household with an unemployed father during the Great Depression or high levels of environmental contaminants exposure are representative of the Second D. Height velocity at specific ages and weight loss in postmenopausal years are illustrative of anthropometric trajectories that reveal an adaptive biosystem that provides a contextual state to interact with the other two Ds. This article presents a new paradigm of nutrition and breast cancer prevention through the lens of three very different dimensions. It is the premise of this article that all three dimensions are essential tasks to tease apart the life course and identify windows for preventive strategies.